Evaluation of the government support price for palay producers in Dumangas and Sara, Province of Iloilo - Cambas, Oliver L (Iloilo City U.P. in the Visayas, 2007)
The purpose of the government support price is to give palay producers the option to sell their products even when farm gate prices are low. It also aims to minimize abrupt fluctuation of palay buying prices. The government support price does not aim to control the market or compete in it, but rather to give an equal plying field for farmers. Despite f this support, price, however, the farmer's living condition has never changed. Questions arise as to whetheor not this support price can give sufficient income to farmers to meet their basic need. This study aims to evaluate the government support price for palay producers. Specifically, it seeksto find out whether if this support price can give farmers the sufficient income to farmers to meet their basic need. Chi-square test was used to determine the significance of the respondents' profiles with their annual net income. To prove that the government support price progrm is beneficial in the palay industry, cost-benefit analysis was conducted. And in assessing the support price, respondents' annual net income was computed and compared to the required annual income. Results reveal that the respondents' age, household size, farm area, fertilizer used, source of water, mode in planting, annual production, and annual expenses have significant relationship with their annual net income.Results reveal that the respondents' age, household size, farmarea, fertilizer used, source of water, mode in planting, annual production, and annual expenses have significant relationship with their annual net income. Furthermore, the studyshows that the program is beneficial to palay farming. However, the P10.00/kg government support price produces insufficient net income to sustain the basic needs of the farmers withland area of three hectares and below. Only the land area with above three hectares farm can meet the required annual income per capita which is P14,031 in the Province of Iloilo. Thresearcher recommends that first, the average area of land cultivated by farmers should be considered as a factor in determining the government support price. The study reveals that most farmers earn their livelihood from cultivating three hectares of farmland or below. These are also the farmers who fall short of the required annual income. And second, the support price should be periodically evaluated by the inter-agency Technical Working Group. The P10.00/kg support price was approved and implemented in 1999 and has remained the same in 2006.
"Final report (Research Methods in Management)"